Adoption of new technologies: A study with non-users of the CPF issuance request system on the internet, with emphasis on sociodemographic aspects - Souza, Nery Domingos Gomes de; Farias, Josivania Silva (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
This study analyzed factors determining the non-adoption of the CPF delivering service made available digitally, distinguishing non-adopting citizens due to demographic variables and technology usage habits. Theoretical basis was the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2). The descriptive quantitative study obtained a sample of 383 postal customers. The instrument's internal consistency was assessed by Cronbach's Alpha, Pearson and Spearman correlations between variables were analyzed, in addition to tests: Student's T, ANOVA and Chi-square. It was concluded that there is a complexity to meet user needs given the demographic characteristics existing in Brazil. The study recommends actions that lead to the development of more intuitive platforms, which may increase the diffusion of the digital platform.